Simple Step Add-in to Improve Patient Safety: A Technical Note - Elgabaly, Elham A (Cureus, 2020)
Human factors and systems factors can affect surgical performance, including the operating room (OR) environment, teamwork and communication, technology and equipment, tasks and workload factors, and organizational variables. Patient safety is a new healthcare discipline that emphasizes the reporting, analysis, and prevention of medical errors that often lead to adverse healthcare events. We are highlighting a potential error and hazardous situation, which may occur due to the difficulty in reading the embossed letters of some ampoules because of the typeface of these ampoules. This problem is particularly important in the ORs, which require special sterile conditions. We are adding a simple step to help in the differentiation between plastic, embossed ampoules. This simple and easy-to-do step makes it possible for accurate and correct identification, without jeopardizing the safety of the patients and health care professionals.